Applications of Molecular Spectroscopy to Current Research in the Chemical and Biological Sciences - Stauffer, Mark T. (IntechOpen, 2016)
The goal of this book is to present an overview of applications of molecular spectroscopy to investigations in organic and inorganic materials, foodstuffs, biosamples and biomedicine, and novel characterization and quantitation methods. This text is a compilation of selected research articles and reviews covering current efforts in various applications of molecular spectroscopy. Sections 1 and 2 deal, respectively, with spectroscopic studies of inorganic and organic materials. Section 3 provides applications of molecular spectroscopy to biosamples and biomedicine. Section 4 explores spectroscopic characterization and quantitation of foods and beverages. Lastly, Section 5 presents research on novel spectroscopic methodologies. Overall, this book should be a great source of scientific information for anyone involved in characterization, quantitation, and method development.